Internalisasi Nilai-Nilai Pendidikan Kewirausahaan dalam Kurikulum di SMK Salafiyah Syafi’iyah - Nurhamidah Nurhamidah (Pascasarjana IAIN Sultan Amai Gorontalo, 2018)
This article shows that the internalization of the values of entrepreneurship education in subjects has been implemented, namely the inclusion of these values into learning planning and syllabus, even though the implementation of learning with all the limitations of teachers who are not educational in accordance with the subject matter is effective, and has seen changes in the attitude of students in learning from planting five values of creative and independent entrepreneurship, but in terms of evaluation of learning it has not referred to standardized assessment standards.